Exacerbation of demyelinating polyneuropathy after adoptive cell therapy with tumour-infiltrating lymphocytes by metastatic melanoma (Swiss Medical Weekly, 2025)
Adoptive cell therapy (ACT) with tumour-infiltrating lymphocytes (TIL) is an effective personalised immunotherapy for patients with advanced pretreated melanoma. For TIL-ACT, tumour-specific T cells are expanded from excised tumour samples and stimulated in cell culture with interleukin-2 (IL-2). The resulting autologous tumour-infiltrating lymphocytes are reinfused to the patient after a non-myeloablative lymphodepleting chemotherapy with cyclophosphamide and fludarabine. Thereafter, activation of tumour-infiltrating lymphocytes in the patient is supported by the administration of high-dose IL-2. Although effective, there is a need for enhancement of TIL-ACT in terms of effectiveness and toxicity. Most of the toxicity in this multistep, complex treatment regimen is due to the preparative chemotherapy and high-dose IL-2 treatment. At University Hospital Basel, we are currently evaluating an experimental approach of TIL-ACT in which we replace high-dose IL-2 by in vivo tumour-infiltrating lymphocyte activation with ANV419, a novel antibody-cytokine fusion protein consisting of IL-2 fused to an anti-IL-2 monoclonal antibody, in an ongoing phase I trial (BaseTIL-03M). The primary endpoint of the study is safety.We herein describe the case of a patient included in the BaseTIL-03M trial with chronic inflammatory demyelinating polyneuropathy who received TIL-ACT with ANV419 and developed an acute polyneuropathy of Guillain-Barré syndrome.